Wage Indexation and the Cost of Disinflation - Jadresic, Esteban (IMF Working Papers; Working Paper, 1996)
While a standard academic presumption has been that wage indexation reduces the cost of disinflation, policymakers generally contend that wage indexing makes disinflation more difficult. To shed light on these views, this paper reexamines the effects of wage indexing on the output loss caused by money-based stabilization. It finds that the cost of disinflation with indexed wage contracts tends to be smaller than that with contracts that specify preset time-varying wages, but larger than that with contracts that specify fixed wages. Thus the academic and policymakers views can be both appropriate depending on the standard of reference.